PCSMAC: A power controlled sensor-MAC protocol for wireless sensor networks - Nar, Pelin C.; Cayirci, Erdal (IEEE, 2005)
In this paper a new power controlled contention-based MAC protocol is introduced for wireless sensor networks where sensor nodes can adjust their transmission power level on a per-frame basis. The main contribution of our work is to enable power controlled transmission of RTS, CTS, DATA and ACK frames while preserving the collision and overhearing avoidance properties of a MAC protocol where these frames are transmitted at the maximum power. Experimental results show that the power controlled sensor MAC protocol reduces the energy consumption by 30-99% comparing to the conventional sensor MAC protocol.